Macronutrient and calorie content in preterm and term human milk at first three week after delivery - Dessy Shinta Murty; Hasriza Eka Putra; Sri Mulatsih; Neti Nurani; Tunjung Wibowo (Paediatrica Indonesiana, 2019)
Background The macronutrients in human milk change dynamically and vary among mothers. Evaluation of macronutrient content in human milk is needed to improve nutritional management in preterm infants. Objective To measure the macronutrient content in preterm and full term human milk during three lactation periods in the first three weeks after delivery. Methods We conducted a prospective study among 80 mothers of infants who were hospitalized in the Department of Perinatology/NICU at Sardjito Hospital, Yogyakarta. Carbohydrate, fat, protein, and caloric content were measured using a MIRIS human milk analyzer, once per week for three consecutive weeks after delivery. A single, daytime human milk specimen was collected in the morning by directly expressing from the breast. Results Median protein, fat, carbohydrate, and caloric contents of mature milk in the preterm group were 1.40 (IQR 0.38), 3.25 (IQR 1.00), 5.70 (IQR 0.80) g/dL, and 60 kcal/dL, respectively. Median protein, fat, carbohydrate, and caloric contents of mature milk in the full term group were 1.40 (IQR 0.35), 3.30 (IQR 0.77), 5.80 (IQR 0.75) g/dL, and 62 kcal/dL, respectively, at the third week after delivery. In both groups, protein content in the first week was significantly higher than in the third week (P<0.001) after delivery. In contrast, fat content in the first week was significantly lower than in the third week (P< 0.05) after delivery, in both groups. Conclusions There are no significant differences in macronutrient and caloric content between preterm and full term human milk during the first three weeks after delivery. However, there are significant changes in fat and protein content in both preterm and full term human milk during early lactation, between the first and third weeks.